Effect of the time of carbohydrate intake on muscle glycogen recovery post-exercise - Ouchi, S.; Shiose, K.; Osawa, T.; Motonaga, K.; Kamei, A.; Kawahara, T.; Taguchi, M.; Takahashi, H. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
Muscle glycogen synthesis rate is lowered when post-exercise CHO ingestion is delayed 2 hours compared with CHO ingestion immediately post-exercise. However, effect of CHO intake at 1 hour post-exercise on muscle glycogen recovery, is not clear. The purpose of this study was to evaluate the effect of the time of CHO intake on post-exercise muscle glycogen recovery. Six male endurance-trained athletes (age: 21±2 y; height: 170±8 cm; body mass: 61.3 ± 5.7 kg) consumed CHO (2.0 g/kg body weight) either immediately post-exercise (P-EX) or 60 minutes post-exercise (60P-EX) after a time trial (TT) on a cycle ergometer at 70% maximum power for approximately 60 min (842 ± 50 kJ)